Introduction of a Surgical Navigator in the Perioperative Process Improves Patient Satisfaction - Brett G Marshall; Maija S Assef; Ryan B Pitney; Maria CJ Macco; Bradley M Tschoeke; Marcus A Oksa MS, RCP; Amy Yeatman DO (Journal of Patient Experience, 2017)
Background: Patients who had received surgical services at Bellin Hospital reported anxiety with the surgical flow. This study tested the hypothesis that the introduction of a surgical navigator, someone who guided the patient and their accompanying others throughout the surgical process, would improve patient satisfaction. Methods: Ambulatory surgical patients were randomized to control and study groups. The study group patients were assigned a surgical navigator. Prior to discharge from the hospital, patients were asked to complete a patient satisfaction survey. Results: The study group had significantly higher mean scores ( P value ≤ 0.026), top box scores ( P value ≤ 0.021), and positive comments. Conclusion: The addition of a surgical navigator to the perioperative process significantly enhanced patient satisfaction in ambulatory surgical patients.